2019
DOI: 10.4103/apc.apc_89_18
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous aortic origin of the pulmonary arteries: Case series and literature review

Abstract: Anomalous origin of the pulmonary arteries from the ascending aorta is a rare, but severe clinical entity necessitating a scrupulous evaluation. Either the right or the left pulmonary arteries can arise directly from the ascending aorta while the other pulmonary artery retains its origin from the right ventricular outflow tract. Such a finding can be isolated or can coexist with several congenital heart lesions. Direct intrapericardial aortic origin, however, must be distinguished with origin through a persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Unequal partitioning of the "conotruncus" by eccentric coalescence of the right and left outflow tract ridges can similarly be discounted since the outflow cushions separate the intermediate and proximal parts of the developing outflow tract. 4 Lesions such as aortopulmonary window, or an anomalous origin of the right pulmonary artery from the aorta, are intrapericardial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unequal partitioning of the "conotruncus" by eccentric coalescence of the right and left outflow tract ridges can similarly be discounted since the outflow cushions separate the intermediate and proximal parts of the developing outflow tract. 4 Lesions such as aortopulmonary window, or an anomalous origin of the right pulmonary artery from the aorta, are intrapericardial.…”
Section: Discussionmentioning
confidence: 99%
“…The term Hemitruncus is considered inadequate as per professor Anderson et al 3 because unlike—truncus arteriosus—two arterial valves aortic and pulmonary are present. About 300 cases have been reported in the literature, most of them in relation to surgical correction 4 . Choosing the appropriate technique for repair depends on the site of origin of the anomalous pulmonary artery from aorta.…”
Section: Introductionmentioning
confidence: 99%
“…In the disease, the pulmonary pressure increases with time and the mortality rate varies from 30% to 70% depending on case severity and receiving cardiac surgery as soon as possible. [1][2][3][4][5][6][7][8] Early surgical repair can prevent pulmonary vascular disease progression. 4 The surgical repair should be done within the first six months to prevent severe pulmonary vasculature disease.…”
Section: Discussionmentioning
confidence: 99%
“…2 It can occur in isolation or in association with other anomalies. 3 It affects more commonly the RPA. The AAOBPA is usually intrapericardial, which should differentiate this from other sources of pulmonary blood flow such as ductal origin of the pulmonary artery or major aortopulmonary collateral artery.…”
Section: Commentmentioning
confidence: 99%
“…It is the unequal separation of the aortic sac itself that may provide a better explanation to this anomalous pulmonary artery branch origin. 8 In a recent review, 3 299 patients were reported with AAOBPA from 1962 to 2017, with repair performed in 73% of them. None of these cases reported any acute event in the anomalous artery such as in the current case where a dissection flap and thrombi were identified in the RPA, which explains the inability to identify the artery on preoperative CTA scan or echocardiogram due to near absence of forward flow from the aorta.…”
Section: Commentmentioning
confidence: 99%